Transformation of Retail Trade in the Digital Era: A Bibliographic Analysis of the Impact of E-commerce on Emerging Economies (National Administration Journal, 2025)
This article is an analysis form the bibliographic perspective on the transformation of the retail trade, in addition to the impact that has been generated with the arrival of E-commerce, taking as a starting point some historical antecedents of traditional commerce, so this study is of critical and reflective characteristics, taking as a reference scientific articles, books on the subject, in addition to publications on websites, which leads to taking into account the change that business models have been presenting in recent years. Another factor to considerer is that with the entry of the digital era, there is an acceleration in the transformation of companies, giving in itself an advance of ten years of evolution, the research also presents a descriptive table that refers to the main types of business derived from electronic commerce and also includes, an interview with a specialist in the subject, providing his points of view, on retail and its reinvention in the digital age.
Keywords: comercio electrónico; comercio minorista; B2B; B2C; C2C; redes sociales; transferencias electrónicas